Aristotle and hermeneutics - Soto Isaza, Diego (Estudios de Filosofía, 2001)
Application and incorporation of the interpretation and understanding give unity to the hermeneutic question, in so far as they are inseparable of the understanting itself as a singlep rocess. The concept of "application", the third moment of the theory of Interpretation that Gadamer returned to the central place it deserves in the philosophical hermeneutics, is especially designed on the basis of the Aristotelic practical science and on the exercising of the phrónesis which is its main virtue.